Successful Management of Prepartum Vaginal Prolapse in Crossbreed Hf Cattle - Zeenath Fathima; Shaik Aamer; Satish Martha; M.Rajashri; E.Sunil Anand Kumar (The Indian Veterinary Journal, 2023)
A pleuriparous crossbreed HF cow was presented with the history of vaginal prolapse during last trimester of pregnancy. Successful management of prepartum vaginal prolapse using rope truss technique and Buhner’s sutures was reported.